If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = 4x Reorder the terms: -8 + x = 4x Solving -8 + x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + x + -4x = 4x + -4x Combine like terms: x + -4x = -3x -8 + -3x = 4x + -4x Combine like terms: 4x + -4x = 0 -8 + -3x = 0 Add '8' to each side of the equation. -8 + 8 + -3x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 0 + 8 -3x = 0 + 8 Combine like terms: 0 + 8 = 8 -3x = 8 Divide each side by '-3'. x = -2.666666667 Simplifying x = -2.666666667
| 9x^2=51x-60 | | 6(t-5)+8t=7(2t+4)-11 | | 5t+2+4t-8t=5+5 | | 4(x-3)=-(x+7) | | (x-5)(x+3)(x+4)=0 | | x-(x+1)=12-(3x-2) | | y=x^2-x-23 | | 4(9v+2)=6(1+6v)-10 | | 2x=x+65 | | -2(c-d)+(c-3d)-5(c-d)= | | -0.5x^2+2x-70=0 | | 6a+4=a+7 | | -20x^2-8x+64=0 | | 2n^2+33n-17=0 | | 2.5x+0.25x=0.75+x | | 4x+9=3x+5 | | 6m^2=23m-15 | | 0.36(18)+0.04x=0.12(6+x) | | -2x+3y-5x-(-8y)+9y= | | 4+2x*6=x*-10+2 | | 9x^2=33x-30 | | 8x=3x-45 | | 4m^2-12m+9=0 | | -7-3y=8 | | 201-2x=43+16 | | 8x-51=3x | | 5-4y+x+9y= | | 4x+13=-7-9x | | 155-6x=4x | | 4(x+5y)+(5x+y)= | | 1.23x+0.125x=0.375+x | | x+8=6-3x |